Analisis Perwilayahan Komoditi Jagung (Zea mays L.) Berbasis Produksi di Kecamatan Bualemo Kabupaten Banggai - Ambo Abd Kadir Pakanyamong; Hidayat Arismunandar Katili (Fakultas Pertanian, Universitas Timor, 2023)
Corn is one of the agricultural commodities that specializes in food crops that are cultivated by the community as one of the staple foods to replace rice. In terms of the economy, corn is a commodity that can generate profits for farmers. So, this study aims to find out the village that is the flagship of corn commodities (Zea mays L) in Bualemo District so that it becomes the input to stakeholders regarding the importance of development in the corn crop base area in supporting economic growth in Bualemo District. This research uses the method of service economics (Base Analysis, Localization Analysis, and Specialization Analysis). The results showed that the analysis of the maize crop base in the Bualemo District of Banggai Regency had obtained 11 villages (77%) which became the base and non-base ones obtained 6 villages (23%). This means that the village that is the base of the corn crop is an area that can meet the needs of its region and other regions. Furthermore, the analysis of the localization of corn crops in the Bualemo District area obtained a small localization efficiency from one (α < 1), which means that corn commodities in the Bualemo District have spread throughout the area of the villages. As well as the analysis of the specialization of corn commodities in the Bualemo District area, the results were obtained, namely (β < 1), which means that the corn crop is not a crop that specializes in the Bualemo Kecamtan area.